2013
DOI: 10.1103/physrevlett.111.016401
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Charge Recombination in a Photoexcited Mott-Hubbard Insulator

Abstract: We present a calculation of the recombination rate of the excited holon-doublon pairs based on the two-dimensional model relevant for undoped cuprates, which shows that fast processes, observed in pump-probe experiments on Mott-Hubbard insulators in the picosecond range, can be explained even quantitatively with the multimagnon emission. The precondition is the existence of the Mott-Hubbard bound exciton of the s-type. We find that its decay is exponentially dependent on the Mott-Hubbard gap and on the magnon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
116
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 38 publications
4
116
0
Order By: Relevance
“…In the absence of such a bath the only possible decay paths involve kinetic energy transfer (creation of particle-hole pairs) or spin excitations within the Hubbard model itself, where the relevant energy scales are the bandwidth t and the exchange coupling t 2 =ðU − VÞ, respectively [17]. For U ≫ V, t a large number of scattering events is required for recombination, leading to a decay rate that is exponentially small with U=t [17][18][19][20]. Owing to the weak electronphonon coupling in ET-F 2 TCNQ [5], and lack of efficient radiative emission, it is reasonable to assume that highfrequency molecular modes are the primary scattering partner for the rapid decay of hot quasiparticles observed in our experiment.…”
Section: (D)mentioning
confidence: 99%
“…In the absence of such a bath the only possible decay paths involve kinetic energy transfer (creation of particle-hole pairs) or spin excitations within the Hubbard model itself, where the relevant energy scales are the bandwidth t and the exchange coupling t 2 =ðU − VÞ, respectively [17]. For U ≫ V, t a large number of scattering events is required for recombination, leading to a decay rate that is exponentially small with U=t [17][18][19][20]. Owing to the weak electronphonon coupling in ET-F 2 TCNQ [5], and lack of efficient radiative emission, it is reasonable to assume that highfrequency molecular modes are the primary scattering partner for the rapid decay of hot quasiparticles observed in our experiment.…”
Section: (D)mentioning
confidence: 99%
“…Many recent studies focused on dynamics of photo-induced carriers, i.e., doublons and holons [27][28][29][30][31][32][33][34][35][36][37][38], in particular on their nonradiative recombination process [37][38][39][40][41][42][43]. Experimentally, photo-induced carriers have been observed in, e.g., insulating cuprates, where they decay within a few hundreds of femtoseconds [44].…”
mentioning
confidence: 99%
“…It was recently demonstrated that after such an interaction quench the order parameter m quickly relaxes to a quasistationary but nonthermal value [17] that is protected from further decay by the slow recombination rate of doublons and holes [27][28][29][30]. This transient state resembles properties of a photodoped system in which charge carriers are created by a short laser pulse.…”
mentioning
confidence: 99%